Recent Advances in the Synthetic Application of Difluorocarbene - Ni, Chuanfa; Hu, Jinbo (Synthesis, 2014)
Difluorocarbene is a versatile, reactive intermediate for use in organic synthesis. Over the past decade, significant progress has been made in difluorocarbene chemistry owing to the increasing demand for various fluorinated molecules. Not only the substrate scope for some classical difluorocarbene reagents has been largely expanded, but also new and environmentally friendly difluorocarbene reagents for difluoromethylation and gem-difluorocyclization have been developed. This review summarizes the difluoromethylation, gem-difluorocyclopropanation, gem-difluorocyclopropenation, gem-difluoroolefination, and trifluoromethylation achieved in the last decade using both the classical and the new difluorocarbene sources.1 Introduction2 Difluorocarbene Sources3 Difluoromethylation3.1 O-Difluoromethylation3.2 S-Difluoromethylation3.3 N-Difluoromethylation3.4 Difluoromethylation of Ambident N,O- and N,S-Nucleophiles 3.5 Se- and P-Difluoromethylation3.6 C-Difluoromethylation3.7 Sn-Difluoromethylation4 gem-Difluorocyclization4.1 gem-Difluorocyclopropanation4.2 gem-Difluorocyclopropenation5 gem-Difluoroolefination and Related Reactions6 Trifluoromethylation7 Miscellaneous8 Conclusions
Keywords: difluorocarbene; difluoromethylation; cycloaddition; gem-difluoroolefination; trifluoromethylation